Development of a PBL-based interactive e-module to improve students’ knowledge, attitudes, and balanced nutrition behavior - Ngurah Mahendra Dinatha; Bernadethe Ines Sede Pajo (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Adolescence is an important period in the formation of eating habits, yet many junior high school students still have a limited understanding of balanced nutrition and tend to adopt unhealthy eating patterns. This condition indicates the need for learning media that are more active, contextual, and suited to adolescents’ digital characteristics. Objective: To develop and evaluate an interactive health education e-module based on Problem-Based Learning to improve knowledge, attitudes, and healthy behavioral intentions related to balanced nutrition. Methods: This study employed a Research and Development approach using the ADDIE model. The participants were 60 seventh- and eighth-grade students at SMPN 2 Bajawa. The product was evaluated through expert validation, practicality testing, and effectiveness testing using a quasi-experimental non-equivalent control group design, in which the experimental group used the PBL-based e-module while the control group received conventional instruction. Data were analyzed using Aiken’s V, descriptive statistics, N-Gain, and significance tests. Results: The PBL-based interactive e-module demonstrated high validity (Aiken’s V = 0.89) and practicality (89.6%). It was also effective in improving knowledge, attitudes, and healthy behavioral intentions, with a higher average N-Gain in the experimental group (0.66) than in the control group (0.24). Significant differences in post-test scores were found between groups (p < 0.001). Conclusion: The developed interactive PBL-based e-module was proven to be valid, practical, and effective in supporting balanced nutrition education through active, contextual, and reflective learning among Indonesian junior high school students.